The hydrodynamic relationships of two herbaceous species in a grazed Morus alba L. silvopastoral system - Sklavou P.S.; Karatassiou M.; Tsiouvaras C.N.; Noitsakis B. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
In most Mediterranean areas water is one of the major determinants of plant growth. The water relations of herbaceous species was studied in a Morus alba L. silvopastoral system under moderate grazing. The experimental area was divided into six fenced plots in order to exclude uncontrolled grazing. Three of them were randomly assigned to be grazed (0.9 sheep/ha/year) while the other three remained ungrazed. Half of every plot was ploughed and seeded with Trifolium subterraneum cv Mt. Barker while the other half remained with the natural herbaceous vegetation. The water potential (Ψ) and relative water content (RWC) of T. subterraneum and of the dominant native grass Poa bulbosa were measured. Although grazing does not modify the internal water status of T. subterraneum and P. bulbosa, both species seem to have the ability to control their water balance probably by pathetic regulation of osmosis.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)